Non-Hodgkin Lymphoma With Longitudinally Extensive Transverse Myelopathy as the Initial Symptom: A Case Report - Chen, Yanxing; Lin, Caixiu; Zhang, Baorong (Frontiers in Oncology, 2019)
Identifying lymphoma as the cause of neurological disease is diagnostically challenging when the clinical manifestations are atypical. We report an unusual case of a previously healthy immunocompetent 67-years-old man presenting with acute onset of symptoms of myelopathy and mild personality changes. Magnetic resonance imaging (MRI) revealed multifocal periventricular lesions and longitudinally extensive transverse myelitis (LETM). He had very good response to corticosteroids and was in remission for over 6 months. Repeat MRI showed an unexpected mass lesion in the brain which was later confirmed by brain biopsy as diffuse large B cell lymphoma. Subsequent FDG-PET/CT revealed systemic disease with lymphonodal and testicular manifestations (Stage IV disease). It is therefore important to consider lymphoma as a differential diagnosis in patients with LETM and demyelinating lesions in the brain.